2019
DOI: 10.1097/dbp.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Screen Use, Sleep, and Emotional/Behavioral Difficulties in Preschool Children with Neurodevelopmental Disorders

Abstract: Objective: Despite evidence that excessive screen use may contribute to negative health, developmental, emotional, and behavioral outcomes, more children are engaging in increasing amounts of screen-related activities. For children with neurodevelopmental conditions, increased screen use could exacerbate emotional/behavioral difficulties (EBDs) by interfering with sleep quantity and quality. Aims: This study examined the possible mediating role of sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
1
21
0
5
Order By: Relevance
“…Another study explained the relationships between inactivity, ST, and psychosocial di culties as bidirectional [56]. In addition, children who suffered from neurodevelopmental disorders had more di culties disengaging from screen devices, which could exacerbate emotional/behavioral di culties [57]. Similarly, our ndings support the conclusion that high ST has adverse effects on the EBHPs of children and adolescents [58].…”
Section: Discussionsupporting
confidence: 80%
“…Another study explained the relationships between inactivity, ST, and psychosocial di culties as bidirectional [56]. In addition, children who suffered from neurodevelopmental disorders had more di culties disengaging from screen devices, which could exacerbate emotional/behavioral di culties [57]. Similarly, our ndings support the conclusion that high ST has adverse effects on the EBHPs of children and adolescents [58].…”
Section: Discussionsupporting
confidence: 80%
“…10 Screen exposure is significantly associated with SPs, and it has been demonstrated that SPs serve as a liaison between screen use and behavioral problems. 9,33 Therefore, the approach to this situation is very important in children with DDs, who have a higher risk for screen use, trouble to "let go", and light sensitivity. 9 In our population, the total number of sleep hours was between the 2 nd and 10 th percentiles 4,10,13 a n d i n t h e l o w e s t r a n g e o f t h e v a l u e s recommended by the American Association of Sleep Medicine.…”
Section: Discussionmentioning
confidence: 99%
“…9,33 Therefore, the approach to this situation is very important in children with DDs, who have a higher risk for screen use, trouble to "let go", and light sensitivity. 9 In our population, the total number of sleep hours was between the 2 nd and 10 th percentiles 4,10,13 a n d i n t h e l o w e s t r a n g e o f t h e v a l u e s recommended by the American Association of Sleep Medicine. 34 Our study is consistent with the bibliography in terms of the significant association between SPs and co-sleeping, but it is difficult to establish the trend of such association.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] It has been confirmed by accumulating studies that short sleep duration and sleep disturbance have negative impacts upon a range of aspects including metabolic balance, neurobehavioral function, and mental health. [2][3][4][5][6][7] To date, a large number of factors have been reported affect children's sleep. However, almost all studies focused on children's own environmental exposure, lifestyle factors, and health condition, such as family members' interaction, sleep environment, physical activity, obesity, etc.…”
Section: Introductionmentioning
confidence: 99%